Transcription factors regulate GPR91-mediated expression of VEGF in hypoxia-induced retinopathy - Li, Tingting (Sci Rep, 2017)
Hypoxia is the most important factor in the pathogenesis of diabetic retinopathy (DR). Our previous studies demonstrated that G protein-coupled receptor 91(GPR91) participated in the regulation of vascular endothelial growth factor (VEGF) secretion in DR. The present study induced OIR model in newborn rats using exposure to alternating 24-hour episodes of 50% and 12% oxygen for 14 days. Treatment with GPR91 shRNA attenuated the retinal avascular area, abnormal neovascularization and pericyte loss. Western blot and qRT-PCR demonstrated that CoCl(2) exposure promoted VEGF expression and secretion, activated the ERK1/2 signaling pathways and upregulated C/EBP and AP-1. Knockdown of GPR91 inhibited ERK1/2 activity. GPR91 siRNA transduction and the ERK1/2 inhibitor U0126 inhibited the increases in C/EBP β, C/EBP δ, c-Fos and HIF-1α. Luciferase reporter assays and a chromatin immunoprecipitation (ChIP) assay demonstrated that C/EBP β and c-Fos bound the functional transcriptional factor binding site in the region of the VEGF promoter, but not C/EBP δ. Knockdown of C/EBP β and c-Fos using RNAi reduced VEGF expression. Our data suggest that activation of the GPR91-ERK1/2-C/EBP β (c-Fos, HIF-1α) signaling pathway plays a tonic role in regulating VEGF transcription in rat retinal ganglion cells.